Health-seeking behaviour of patients diagnosed with Chronic Kidney Disease with uncertain etiology: Complementary system for health service delivery - Liyanage, J.H.C. (University of Colombo, 2017)
Chronic Kidney Disease with uncertain etiology (CKDu) has been a hazard in the North Central Province and surrounding areas since the late 1990s and early 2000s. Scientists from diverse disciplines have been attempting to identify the etiology of CKDu but have not reached concrete conclusions. The objective of this paper is to explore the health-seeking behaviour of CKDu patients and their illness-management strategies at different stages of disease progression. An ethnographic study was conducted in Madhawachchiya and Padaviya DS Divisions. The study sample included 90 patients, caretakers, community leaders, and healthcare providers. Illness narratives were collected using a phenomenological perspective. In-depth interviews, focus group discussions, key-informant interviews, and observations were used for data collection. Ninety percent of patients were diagnosed with CKDu when they sought treatment for different disorders. Only 10% were diagnosed using screening programmes. Health-seeking behaviour was scrutinized and was seen as a process of illness response from a social behaviour perspective. Two interrelated trends have been emerging. Patients have initiated their treatment process by attending CKDu clinics. Simultaneously, a trend of exploring multiple therapeutic options as complementary to biomedicine, where social networks play a key role in sharing relevant information, was observed. Various healers are mushrooming in response to the growing demand. Fifty percent of patients utilize Ayurvedic treatment when the disease progresses. Narratives reveal that Ayurvedic treatment has an ability to manage ill-health and improve the functional capacity of patients. No remarkable disparities based on gender identity were found. The context demands a complementary and integrated approach towards health service delivery. Policy must be altered to make better use of alternative therapies to biomedicine in addressing health hazards.
Keywords: CKDu, uncertainty, integration, complementary